ISTILAH RITUAL SABAT GANTUKNG NIKA MPALAKNG ADAT PERNIKAHAN MASYARAKAT DAYAK KUALATN DUSUN PETEBANG - Yanuarius Gigih Neonbasu; Amriani Amir; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThe purpose of this research is to describe the form of lingual unit terminology Rantual Sabbath Rantual Nika Mpalakng Customary Marriage in Dayak Kualatn Community in Petebang Hamlet. Describe the meaning of the term Native Mpalakng Marriage Sabbath Ritual Marriage for the Qualified Dayak Society in Petebang Hamlet. Describe the cultural meaning in the ritual of the Sabbath Rantual Nika Mpalakng Traditional Wedding Ceremony in Kualatn Dayak Society in Petebang Hamlet. The method in this research is descriptive qualitative. The approach is sociolinguistic. Data collection techniques are competent see involved, free see involved, record, record. Data collection tools are recording paper, questionnaires, stationery, recording devices. The cultural term in the Sabbath Rantual Nika Mpalakng Traditional Marriage Ceremony in the Dayak Kualatn Community in Petebang Hamlet consists of 25 data. Of the 25 data, it is divided into 2 parts, 6 data from Bapama, 19 basalobar data. Data from further research and can be used as objects of cultural heritage that should be preserved and can be used as guidelines in daily communication, especially the user community through local wisdom hidden in this custom.Keywords: Culture, Gantung Nika Malaking, Traditional Marriage, Dayak Kualatn in Petebang Hamlet.